Outcomes of Treatment for Hepatitis C in Primary Care, Compared to Hospital-based Care: A Randomized, Controlled Trial in People Who Inject Drugs. (22nd June 2019) - Wade, Amanda J; Doyle, Joseph S; Gane, Edward; Stedman, Catherine; Draper, Bridget; Iser, David; Roberts, Stuart K; Kemp, William; Petrie, Dennis; Scott, Nick; Higgs, Peter; Agius, Paul A; et al.
Abstract: Background: To achieve the World Health Organization hepatitis C virus (HCV) elimination targets, it is essential to increase access to direct-acting antivirals (DAAs), especially among people who inject drugs (PWID). We aimed to determine the effectiveness of providing DAAs in primary care, compared with hospital-based specialist care. Methods: We randomized PWID with HCV attending primary care sites in Australia or New Zealand to receive DAAs at their primary care site or local hospital (standard of care [SOC]). The primary outcome was to determine whether people treated in primary care had a noninferior rate of sustained virologic response at Week 12 (SVR12), compared to historical controls (consistent with DAA trials at the time of the study design); secondary outcomes included comparisons of treatment initiation, SVR12 rates, and the care cascade by study arm. Results: We recruited 140 participants and randomized 136: 70 to the primary care arm and 66 to the SOC arm. The SVR12 rate (100%, 95% confidence interval [CI] 87.7–100) of people treated in primary care was noninferior when compared to historical controls (85% assumed). An intention-to-treat analysis revealed that the proportion of participants commencing treatment in the primary care arm (75%, 43/57) was significantly higher than in the SOC arm (34%, 18/53; P < .001; relative risk [RR] 2.48, 95% CI 1.54–3.95), and the proportion of participants with SVR12 was significantly higher in the primary care arm, compared to in the SOC arm (49% [28/57] and 30% [16/53], respectively; P = .043; RR 1.63, 95% CI 1.0–2.65). Conclusions: Providing HCV treatment in primary care increases treatment uptake and cure rates. Approaches that increase treatment uptake among PWID will accelerate elimination strategies. Clinical Trials Registration: NCT02555475. Abstract : Providing direct-acting antivirals for hepatitis C virus in primary care significantly increases treatment uptake and cure rates in people who inject drugs, compared to referral to hospital-based services. Hepatitis C treatment should be available in primary care.